2015
DOI: 10.1103/physrevb.92.155310
|View full text |Cite|
|
Sign up to set email alerts
|

Sudden stress relaxation in compound semiconductor thin films triggered by secondary phase segregation

Abstract: In polycrystalline compound semiconductor thin lms, structural defects such as grain boundaries as well as lateral stress can form during lm growth, which may deteriorate their electronic performance and mechanical stability. In Cu-based chalcogenide semiconductors such as Cu(In, Ga)Se2 or Cu2ZnSn(S, Se)4, temporary Cu excess during lm growth leads to improved microstructure such as a reduced grain boundary density, a strategy that has been used for decades for high-eciency chalcopyrite thin lm solar cells. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…This likely indicates a higher porosity of the MBE‐deposited precursors, allowing a fast diffusion of the Se vapors towards the back contact, which could be controlled to some extent by the Se vapor pressure as will be shown below. A reasonable explanation for the different grain growth could be the different nature of the MBE and sputtered precursors; indeed, compared to the former, sputtered films are typically more compact with reasonably higher compressive stress, which is known to act as a driven force for the grain growth during the annealing treatment …”
Section: Resultsmentioning
confidence: 99%
“…This likely indicates a higher porosity of the MBE‐deposited precursors, allowing a fast diffusion of the Se vapors towards the back contact, which could be controlled to some extent by the Se vapor pressure as will be shown below. A reasonable explanation for the different grain growth could be the different nature of the MBE and sputtered precursors; indeed, compared to the former, sputtered films are typically more compact with reasonably higher compressive stress, which is known to act as a driven force for the grain growth during the annealing treatment …”
Section: Resultsmentioning
confidence: 99%
“…It was shown in ref. 27 that relaxation of lateral stress occurs by re-crystallization during the transition from Cu-poor to Cu-rich. However, it should be noted, that this stress relaxation occurs slightly prior to the Cu-saturated regime and that we cannot observe any influence of the relaxation on the optical band gap.…”
Section: Resultsmentioning
confidence: 99%
“…27. The accessible X-ray energy range was 6 to about 80 keV and the diffraction angle was fixed at 2 θ  = 6.301° ± 0.002° for the first detector and 9.722°° ± 0.002° for the second detector.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[67]. It has also been shown that the phase transition between Cu-poor and Cu-rich material is essential for the stress release in the films during growth [68]. It has been long understood that the lower efficiency of Cu-rich solar cells is due to recombination at or near the interface, which limits the open-circuit voltage [64].…”
Section: Ultrathin Cellsmentioning
confidence: 99%